Ionic Selenium and Nanoselenium as Biofortifiers and Stimulators of Plant Metabolism - Víctor García Márquez; Álvaro Morelos Moreno; Adalberto Benavides Mendoza; Julia Medrano Macías (Agronomy, 2020)
Selenium (Se) is an essential element in mammals; however, there is frequently an insufficient intake due to several factors. Different techniques have been used to deal with this problem, such as plant biofortification with Se in its ionic forms and, more recently, at the nanoscale. Additionally, despite the fact that Se is not considered an essential element in plants, it has been shown to stimulate (through still unknown mechanisms) plant metabolism, causing an increase in the synthesis of molecules with reducing power, including enzymes such as glutathione peroxidase, catalase and ascorbate peroxidase as well as non-enzymatic antioxidants such as phenolic compounds, glucosinolates, vitamins and chlorophylls. A positive correlation has also been shown with other essential elements, achieving an increase in tolerance to environmental adversities. This article describes the advances made in the field of the biofortification of horticultural crops with ionic Se and nanoselenium (nSe) from 2009 to 2019. The aspects covered include various concentrations used, the findings made regarding the impact these chemical forms have on plant metabolism, and indications of its participation in the synthesis of primary and secondary metabolites that increase stress tolerance.